UPAYA MENINGKATKAN KEMAMPUAN KOMUNIKASI SISWA KELAS VII di SMP N 1 NGARIBOYO PADA PEMBELAJARAN IPA MELALUI MODEL PEMBELAJARAN PBL (Problem Based Learning) - Reni Linasari; Joko Widiyanto; Luky Rukmini (LPPM STAI Darussalam Lampung, 2023)
AbstractCommunication skills in learning are really needed considering the developmentof an increasingly competitive era. From the results of observations carried outat SMPN 1 Ngariboyo it was stated that students' communication skills were stilllacking in communication skills. Students are not active in learning activities.Then the formulation of the research problem is how are the efforts carried out inimproving the communication skills of class VII students through the PBLlearning model? The purpose of this research was to find out the improvement ofcommunication skills in class VII students. The research method used class actionresearch with 2 cycles. The research data was obtained from observations andtests of communication skills and learning activities in class, the data obtainedwas analyzed using statistics quantitative. Based on the results of observationsthat have been carried out, the results of communication skills in cycle 2 were40%, an increase of 71.37% in cycle 3. Meanwhile, the results of thecommunication skills test obtained a classical completeness score of 23.07% incycle 2 and an increase of 76. 92% in cycle 3. So the researchers drew theconclusion that the problem based learning (PBL) learning model was able toimprove students' communication skills